Fictitious Personas for Interdisciplinary Team Alignment in the Requirements Elicitation Activities - Almeida, Rodrigo L. A.; Paiva, Joseane de O. V.; Gouveia, Thais N.; Barroso, Hugo L.; B. Neto, João; Santos, Ismayle de S.; Evangelista, Aline L. de P.; de Andrade, Luiz Odorico; Barreto, Ivana C. de H. C.; Andrade, Rossana Maria de Castro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Population aging is accompanied by several comorbidities that require the preparation of society to ensure a better quality of life for the elderly. From this scenario, interdisciplinary projects, which align researchers and professionals in the area of health and technology, arise to build solutions that encompass the needs of the elderly, as well as their families, caregivers, and health professionals. This paper shows an experience report on developing this kind of project focusing on the requirements elicitation activities. First, we present a description of the requirements elicitation stage with the identification process of 12 potential requirements for the platform using two techniques: workshop with stakeholders and analysis of functionalities of mobile applications that aimed at the elderlys health. Then, we report the difficulties of team members in reaching a consensus on the definition of end-users and the requirements to be prioritized in the platform to be developed. Lastly, we present our experience on using fictitious personas, created from statistical data and information provided by the health specialists of the elderly, can help the communication between the members of the project, promoting greater consensus and empathy of the interdisciplinary team, assisting and accelerating the decision making on the prioritization of requirements and the definition of end-user.